2020
DOI: 10.1002/joc.6854
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty evaluation of Climatol's adjustment algorithm applied to daily air temperature time series

Abstract: The present study investigated the uncertainty associated with Climatol's adjustment algorithm applied to daily minimum and maximum air temperature. The uncertainty quantification was performed based on several numerical experiments and the benchmark data, that were created in the frame of the INDECIS project. Using a complex approach, the uncertainty was evaluated on different levels of detail (day-today evaluation through formalism of random functions and through six statistical metrics) and time resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(76 reference statements)
2
16
0
1
Order By: Relevance
“…Moreover, annual and seasonal regional trends were almost consistent and significant at the 0.05 level. Climatol homogenization improved the accuracy and reliability of indices' trends, as Skrynyk et al (2021) concluded. Therefore, climate indices were calculated using the daily homogenized series with Climatol.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Moreover, annual and seasonal regional trends were almost consistent and significant at the 0.05 level. Climatol homogenization improved the accuracy and reliability of indices' trends, as Skrynyk et al (2021) concluded. Therefore, climate indices were calculated using the daily homogenized series with Climatol.…”
Section: Discussionmentioning
confidence: 83%
“…Climatol homogenization improved the accuracy and reliability of indices' trends, as Skrynyk et al . (2021) concluded. Therefore, climate indices were calculated using the daily homogenized series with Climatol.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Skrynyk, et al . 50 evaluated the uncertainty associated with Climatol’s adjustment algorithm and reported a better capacity of Climatol to remove systematic errors related to jumps in the means. Domonkos, et al .…”
Section: Introductionmentioning
confidence: 99%